2015
DOI: 10.1007/s00253-015-6786-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of avian β-defensin and Toll-like receptor expression in chickens infected with infectious bronchitis virus

Abstract: The host innate immune response either clears invading viruses or allows the adaptive immune system to establish an effective antiviral response. In this study, both pathogenic (passage 3, P3) and attenuated (P110) infectious bronchitis virus (IBV) strains were used to study the immune responses of chicken to IBV infection. Expression of avian β-defensins (AvBDs) and Toll-like receptors (TLRs) in 16 tissues of chicken were compared at 7 days PI. The results showed that P3 infection upregulated the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 55 publications
6
42
1
Order By: Relevance
“…Fourteen AvBDs have been identified in chickens to date, and are considered as key components of the host innate immune response against pathogens, and potentially provide a link between innate and adaptive immunities. In agreement with the present observations, expression levels of AvBDs were upregulated in tissues of various avian species infected with NDV strains of pigeon or goose origin (Li et al., ; Xu et al., ), as well as with other avian viruses (Ma et al., , ; Xu et al., ). However, differences in their expression levels in chickens infected with different NDV strains have not previously been studied.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fourteen AvBDs have been identified in chickens to date, and are considered as key components of the host innate immune response against pathogens, and potentially provide a link between innate and adaptive immunities. In agreement with the present observations, expression levels of AvBDs were upregulated in tissues of various avian species infected with NDV strains of pigeon or goose origin (Li et al., ; Xu et al., ), as well as with other avian viruses (Ma et al., , ; Xu et al., ). However, differences in their expression levels in chickens infected with different NDV strains have not previously been studied.…”
Section: Discussionsupporting
confidence: 92%
“…Different expression levels of TLRs, cytokines, avian β‐defensins (AvBDs) have been detected in tissues following challenge of chickens, geese, and pigeon with different strains of NDV (Abdel‐Mageed, Isobe, & Yoshimura, ; Li et al., ; Xu et al., ; Yan et al., ). In addition, innate immune response to some other avian virus infection have been also reported, such as innate immunity of duck against duck hepatitis virus (Ma et al., , ), innate immunity of chicken against infectious bronchitis virus (Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory changes in gene expression in the trachea and kidney may be associated with the distinct viral loads at different time points and in different tissues, which depends on the specific IBV strain (Kameka et al, 2014;Xu et al, 2015). Notably, TLR7 and TRIF were significantly upregulated at 21 dpi in both tissues; MAVS was upregulated at 21 dpi; and MDA5, LGP2, and STING were upregulated at 14-28 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Because TLRs, MDA5, and adapter molecules are involved in recognition of IBV RNA (Guo et al, 2008;Cong et al, 2013;Xu et al, 2015), we examined the mRNA dynamics of TLR3, TLR7, MDA5, and downstream signaling molecules at different phases in the trachea and kidneys of IBV-infected chickens. The results showed that in the early phase of infection, both TLR3 and TLR7 transcripts were significantly upregulated in the trachea at 3-8 dpi, but were only upregulated at 5 or 3 dpi in the kidney, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of cytokines in the host response to NDV infection has been demonstrated, the production of HDPs, originally called antimicrobial peptides, and the potential role of HDPs in avian immunity against NDV have not been described. HDPs are a diverse group of small, cationic, and antimicrobial polypeptides mainly expressed by epithelial barriers and immune cells that play an important role in the innate host defense against bacteria, fungi, and some viruses (11)(12)(13)(14). It is well established that HDPs lead to the differentiation, activation, and chemotaxis of multiple types of leukocytes, inhibit lipopolysaccharide (LPS)-induced effects, and enhance phagocytosis, DNA uptake, and wound healing (15)(16)(17).…”
mentioning
confidence: 99%